A method for measuring in vivo finger kinematics using electromagnetic tracking. Issue 11 (15th August 2022) - Tanashi, Ahmed; Haddara, Raneem; Haddara, Mohammad M.; Ferreira, Louis; Lalone, Emily
Abstract: Accurate in vivo measurement of finger joint kinematics is important for evaluation of treatment methods, implant designs, and for the development and validation of computer models of the hand. The main objective of this project was to develop a standardized finger kinematic measurement system employing electromagnetic (EM) tracking to measure in vivo finger motion pathways. A landmark digitization protocol was developed and used in vivo, in a biomechanical study using EM trackers secured to the finger segments. In vivo results for finger flexion/extension showed no significant differences between EM and goniometer results, 5°±3°; p = 0.735.